Large‐Area Epitaxial Film Growth of van der Waals Ferromagnetic Ternary Chalcogenides. Issue 45 (18th September 2021) - Giri, Anupam; De, Chandan; Kumar, Manish; Pal, Monalisa; Lee, Hyun Hwi; Kim, Jun Sung; Cheong, Sang‐Wook; Jeong, Unyong
Abstract: Following the first experimental realization of intrinsic ferromagnetism in 2D van der Waals (vdW) crystals, several ternary metal chalcogenides with unprecedented long‐range ferromagnetic order have been explored. However, the synthesis of large‐area 2D ternary metal chalcogenide thin films is a great challenge, and a generalized synthesis has not been demonstrated yet. Here, a quick and scalable synthesis of epitaxially aligned ferromagnetic ternary metal chalcogenide thin films (Cr2 Ge2 Te6, Cr2 Si2 Te6, Mn3 Si2 Te6 ) is reported. The synthesis is based on the flux‐controlled surface diffusion of Te on metal (Cr, Mn)‐deposited wafer (Ge, Si) substrates. Magnetic anisotropy study of the epitaxial ternary thin films reveals the intrinsic magnetic easy axis; out‐of‐plane direction for Cr2 Ge2 Te6 and Cr2 Si2 Te6, and in‐plane direction for Mn3 Si2 Te6 . In addition to the synthesis, this work creates an opportunity for transfer‐free device fabrication for realizing magnetoelectronics based on the electrical control of both charge and spin degrees of freedom in 2D ferromagnetic semiconductors. Abstract : 2D magnetic crystals constitute ideal platforms to experimentally access the fundamental physics of magnetism and achieve magneto‐optical and magneto‐electric devices for future electronics. In this work, a new generalized synthetic concept for producing wafer‐scale epitaxial thin films of 2D ferromagnetic ternary chalcogenide crystals is described. The growth process utilizes commercial wafers (Ge, Si) as a metal source as well as epitaxy provider.